Factors associated with mental health outcomes among peer refugee helpers in Greece: Results from a cross-sectional study - Michalis Lavdas; Gro Mjeldheim Sandal; Tormod Bøe (SSM - Mental Health)
Background: An increasing number of people are engaged in humanitarian responses worldwide as aid workers. Peer Refugee Helpers (PRHs) are refugees or asylum seekers engaged formally in humanitarian assistance through Aid/Humanitarian Organizations, yet the factors affecting their mental health are poorly understood. Objectives: This study aims to investigate the mental health of PRHs and explore factors that may contribute to anxiety and depression in this group through the lens of the Salutogenic Model of Health (SMH). Methods: A cross-sectional study was conducted comparing PRHs engaged with Aid/Humanitarian Organizations (AOs) in Greece with non-helpers (N = 248), all of whom had experienced forced migration. Standardized instruments were used to measure symptoms of depression and anxiety (GAD-7, PHQ-9), social support (SPS-24), sense of coherence (SOC-13), coping flexibility (PACT), and trauma exposure (BTQ-10). Using regression analyses, we compared symptoms of anxiety and depression in a group of PRHs (n = 107) to a control group of non-helpers (n = 141). Socio-demographic variables (ex. occupational status) were also included in the model. Furthermore, we investigated protective and risk factors for anxiety and depression within the group of PRHs. Results: PRHs did not differ significantly from the non-helpers in their anxiety and depression levels. In the adjusted regression analyses within the group of PRHs, being paid and having a higher sense of coherence were significantly associated with lower anxiety and depression. Conclusions: To enhance the well-being and mental health of refugees working as PRHs in the humanitarian field, AOs should first address post-migration living difficulties that contribute to anxiety and depression. Second, PRHs should be supported adequately through training and supervision that will help them build fundamental competencies. Third, compensation for the PRH engagement is instrumental in addressing job insecurity, while facilitating access to resources, relevant to basic and psychological needs.